Electrical circuits in biomedical engineering : problems with solutions - Keskin, Ali Ümit (Springer, 2017)
This authored monograph presents a comprehensive and in-depth analysis of electrical circuit theory in biomedical engineering, ideally suited as textbook for a course program. The book contains methods and theory, but the topical focus is placed on practical applications of circuit theory, including problems, solutions and case studies. The target audience primarily comprises researchers and experts in electrical engineering who intend to embark on biomedical applications. The book is also very well suited for graduate students in the field.
Keywords: Electric circuits.; Biomedical engineering.; Medical electronics.; elektronické knihy; electronic books